Search for transiting exoplanets and variable stars in the open cluster NGC 7243. Issue 3 (1st March 2016) - Garai, Z.; Pribulla, T.; Hambálek, Ľ.; Errmann, R.; Adam, Ch.; Buder, S.; Butterley, T.; Dhillon, V. S.; Dincel, B.; Gilbert, H.; Ginski, Ch.; Hardy, L. K.; et al.
Abstract: We report results of the first five observing campaigns for the open stellar cluster NGC 7243 in the frame of project Young Exoplanet Transit Initiative (YETI). The project focuses on the monitoring of young and nearby stellar clusters, with the aim to detect young transiting exoplanets and to study other variability phenomena on time‐scales from minutes to years. After five observing campaigns and additional observations during 2013 and 2014, a clear and repeating transit‐like signal was detected in the light curve of J221550.6+495611. Furthermore, we detected and analysed 37 new eclipsing binary stars in the studied region. The best fit parameters and light curves of all systems are given. Finally, we detected and analysed 26 new, presumably pulsating variable stars in the studied region. The follow‐up investigation of these objects, including spectroscopic measurements of the exoplanet candidate, is currently planned. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)